The effect of lifetime aerobic exercise training on memory and IL-1beta cytokine in the hippocampus and prefrontal cortex of NMRI mice with brain trauma - Zahra Shokri; Saeed Naghibi; Ali Barzegari (Shahid Beheshti University, 2022)
Background and Purpose: Brain trauma injury is one of the leading causes of death and disability in the world among all injuries related to the central nervous system. Traumatic brain injury (TBI) is one of the leading causes of death under the age of 40 and accounts for a significant percentage of traumatic deaths. This damage leads to a series of events that depend in part on the nature and location of the injury. Trauma to the head due to the death of neurons in the limbic system, especially the hippocampus, can impair memory and learning function. Therefore, the aim of this study was to evaluate the effect of lifetime aerobic exercise training on memory and cytokine IL-1beta in the hippocampus and prefrontal cortex of NMRI mice with brain trauma.Material and Methods: For this purpose, 40 male NMRI laboratory rats with an approximate age of 20 days and weighing eight to nine grams were prepared from the Pasteur Institute of Iran and divided into four groups: non- exercise + mTBI, non- exercise, exercise and exercise + mTBI.  Rats from 28 days to 80 days of age did aerobic exercise for eight weeks (56 days). At the end of the eighth week after the completion of the exercise protocol, induction of the brain trauma model by weight loss was performed. 10 days after mTBI induction, rats were assessed for spatial memory by maze Y behavioral test. The cytokine IL-1β was evaluated in the hippocampus and peripheral cortex of mTBI mice by ELISA. After checking the normality of the data by Shapiro-Wilk Test and checking the homogeneity of variances by Leven test, One-way analysis of variance was performed by Tukey post hoc test at the significance level of P ≤ 0.05, using SPSS software version 22.Results: The results showed that aerobic exercise had an effect on the memory of mice with brain trauma (P = 0.001). Also, aerobic exercise has an effect on the cytokine IL-1beta in the hippocampus of mice with brain trauma (P = 0.03). In addition, aerobic exercise was shown to have an effect on IL-1beta cytokine in the prefrontal cortex of mice with brain trauma (P = 0.001).Conclusion: This reduction may be due to mechanisms such as low- and high-density lipoproteins, the systemic effects of exercise on neuroprotection, and the reduction of B and T lymphocytes. However, more studies are needed to accurately express the mechanisms of effectiveness. It seems that the exercises used in this study can be used as a therapeutic approach in the treatment of injury and inflammation.